Mathematics Learning Amidst Sit-at-Home Protests: Awareness and Perceptions among Senior Secondary School Students - Darlington Chibueze Duru (Journal of Instructional Mathematics, 2025)
Frequent sit-at-home protests in southeastern Nigeria have disrupted the school calendar and threatened students’ academic progress. This study used a descriptive survey to examine students' awareness and perceptions of sit-at-home protests and their impact on mathematics learning in Orlu LGA, Imo State. Guided by four research questions, the study adopted a descriptive survey design. Data from 116 Senior Secondary School Two (SS2) students in four public schools were collected using the Awareness and Perceptions of Sit-at-Home Protests Questionnaire (APSHPQ), validated by two experts and tested for reliability, and analyzed using mean and standard deviation. Findings revealed that while students were highly aware of sit-at-home protests, their perceptions varied; some viewed the disruptions as necessary for political expression, while others saw them as harmful to their academic progress. Students faced considerable challenges in mathematics learning due to school closures, missed lessons, and limited access to learning resources. Students adopted coping strategies such as online learning, independent study, and catch-up sessions. It was recommended that schools and policymakers integrate flexible digital and blended learning models to sustain instruction. Teachers should offer mobile-friendly resources and virtual support, while schools and parents set structured home-learning schedules to keep students engaged during disruptions.